Analysis of the Application of PSAP No. 13 Concerning Presentation of Public Service Agency Financial Statements at Bhayangkara Tk.III Hospital Manado - Aprilia Korompis; Sonny Pangerapan; Stanley Kho Walandouw (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the suitability of the preparation and presentation of public service agency financial reports at Bhayangkara Tk.III Manado Hospital based on PSAP No. 13. The type of research used is descriptive qualitative. The results of this study indicate that Bhayangkara Hospital Tk.III Manado has implemented PSAP Number 13 as a whole in the preparation and presentation of financial reports on an accrual basis, namely an accounting recording technique where the recording is made when a transaction occurs even though cash has not been received, so as to be able to present transparent financial information and accurate and accountable. One of the important factors supporting the preparation and presentation of financial reports at Bhayangkara Tk.III Manado Hospital is including and presenting LRA, Balance Sheet, LO, LPE, LAK, LP SAL, CaLK., in the procedures for studying financial reports at Bhayangkara Tk.III Hospital Manado